Inflation Dynamics in the Dominican Republic - Williams, Oral.; Adedeji, Olumuyiwa (Washington, D.C. : International Monetary Fund, 2004)
This paper investigates the determinants of inflation in the Dominican Republic during 1991-2002, a period characterized by remarkable macroeconomic stability and growth. By developing a parsimonious and empirically stable error-correction model using quarterly observations, the paper finds that inflation is explained by changes in monetary aggregates, real output, foreign inflation, and the exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet